Decannulation in patients undergoing head and neck cancer surgery: Rapid review - Ana Inês Frade; José Moreira; Lucinda Pires; Marta Duarte; Tiago Cunha; Susana Miguel (Onco.News, 2023)
Introduction: Tracheotomy is commonly used in patients with head and neck cancer undergoing major surgery.